The extent to which middle school teachers possess creative teaching skills - Haidan, Sharifa Saad (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to evaluate the extent to which teachers of the Arabic language at the intermediate stage in the Asir region possess the skills of creative teaching and to achieve this goal the researcher used the descriptive approach, as the researcher prepared a card for observing creative teaching skills, and it consisted of (48) paragraphs and was applied to a sample of language teachers Arabic in the intermediate stage in the Asir region; The number of (15) female teachers. The results of the research showed that the overall tool has obtained an average (1.59 out of 3), with a rating (low), and at the axis level, the axis of creative implementation skills got the highest average (1.84 out of 3), with an estimate (average), and the axis of the creative evaluation of the teachers Average (1.76 out of 3) rated (low), and finally, the creative planning axis got an average (1.18 out of 3) rated (low), and in light of these results the researcher made some recommendations, the most important of which are: Making use of the observation card and its list of skills in building programs Training for Arabic language teachers, and participation of curriculum experts, teaching methods and educational technology in planning, designing, implementing, and evaluating programs Training related to Arabic language teachers.